2020
DOI: 10.1007/s11274-020-02907-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide polymers: no escape to ESKAPE pathogens—a review

Abstract: Antimicrobial resistance (AMR) is one of the significant clinical challenges and also an emerging area of concern arising from nosocomial infections of ESKAPE pathogens, which has been on the rise in both the developed and developing countries alike. These pathogens/superbugs can undergo rapid mutagenesis, which helps them to generate resistance against antimicrobials in addition to the patient's non-adherence to the antibiotic regimen. Sticking to the idea of a 'one-size-fits-all' approach has led to the inap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 58 publications
(64 reference statements)
0
57
0
Order By: Relevance
“…Another study showed that encapsulation of the AMP in dextran nanoparticles increases the residence time in the lungs of the peptide administered via aerosol [ 131 ]. In a recent work, the effective localization of natural AMPs on a negatively charged bacterial surface was described using structurally nanoengineered AMP polymers (SNAPPs) [ 132 ]. In addition, it was proposed to use cubosomes for local delivery of AMPs [ 133 ].…”
Section: Brief History Of Research Physicochemical Properties CLmentioning
confidence: 99%
“…Another study showed that encapsulation of the AMP in dextran nanoparticles increases the residence time in the lungs of the peptide administered via aerosol [ 131 ]. In a recent work, the effective localization of natural AMPs on a negatively charged bacterial surface was described using structurally nanoengineered AMP polymers (SNAPPs) [ 132 ]. In addition, it was proposed to use cubosomes for local delivery of AMPs [ 133 ].…”
Section: Brief History Of Research Physicochemical Properties CLmentioning
confidence: 99%
“…The ESKAPE pathogens ( Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa , and Enterobacter strains) constitute a major concern as they cause numerous infections with limited therapeutic options, and mortality from drug‐resistant strains of these bacteria has increased over the past few years. Therefore, there is a need for the development of some alternative methods for the treatment of antibiotic‐resistant microorganisms [2,3] . For this reason, a therapy that addresses both of these medical problems is particularly interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for the development of some alternative methods for the treatment of antibiotic-resistant microorganisms. [2,3] For this reason, a therapy that addresses both of these medical problems is particularly interesting. Photodynamic therapy (PDT) is a clinically approved approach to the treatment of localized cancer and non-cancer lesions and a perspective modality to treat microbial induced pathologies (photodynamic antimicrobial chemotherapy, PACT).…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of insect antimicrobial peptides as antiviral, antibacterial, and antifungal factors is reported in the literature [ 268 , 269 ]. Synthetic antimicrobial peptides or polymers are attracting significant research attention as an alternative therapy to AMR compared to conventional antimicrobials [ 270 ]. Thus, scope exists to develop novel antimicrobials from such insect antimicrobial peptides, but this aspect warrants further investigation.…”
Section: Future Perspectivesmentioning
confidence: 99%